2021
DOI: 10.6007/ijarbss/v11-i12/11702
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Population Growth and Economic Growth: The Case of Singapore

Abstract: Population growth has an important impact on the economic performance of countries. However, there is no consensus on the direction of the impact in question. Therefore, the relationship between population growth and economic growth is still in debate in the literature. In this context, the aim of this study is to empirically examine whether there is a relationship between population growth and economic growth in Singapore using annual data for the period of 1970-2020. In order to achieve this goal, first of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
1
0
1
Order By: Relevance
“…Regarding population growth effects on the economy, it was found that assuming natural unemployment rate and labor force participation remain unchanged, the reduction in the size of working age population can reduce potential GDP growth rate. (Cai & Lu, 2013) 932 Contrary to this, population growth was found to be a potential driver for economic growth in Singapore under the assumption of good human capital development (Suluk, 2021). From these results, a contrasting view can be seen highlighting a need for further research and analysis.…”
Section: Literature Reviewmentioning
confidence: 93%
“…Regarding population growth effects on the economy, it was found that assuming natural unemployment rate and labor force participation remain unchanged, the reduction in the size of working age population can reduce potential GDP growth rate. (Cai & Lu, 2013) 932 Contrary to this, population growth was found to be a potential driver for economic growth in Singapore under the assumption of good human capital development (Suluk, 2021). From these results, a contrasting view can be seen highlighting a need for further research and analysis.…”
Section: Literature Reviewmentioning
confidence: 93%
“…Analiz edilen ülkeler için bu değişkenler arasında uzun süreli nedensel bir bağlantı olduğu sonucuna ulaşmışlardır. Dahası, Suluk (2021Suluk ( ), 1970Suluk ( -2020 2018) "Nüfus Artışı ve Ekonomik Kalkınma Üzerine Bir Literatür Taraması" başlıklı çalışmasında, geniş bir literatür araştırması yaparak nüfus artışı ve ekonomik gelişme arasındaki ilişkiyi belirlemektedir. Bu konudaki literatür araştırmasından, sürekli artan bir nüfusun bir ülkenin ekonomik kalkınmasına engel gibi görünebileceği, ancak çoğu ülkenin nüfus artışını bir nimet olarak kabul ettiğini belirtmiştir.…”
Section: Li̇teratür Taramasiunclassified